Overcoming Obstacles to the Formulation and Use of Questions in the Science Classroom: Analysis from a Teacher Reflection Workshop - Joglar-Campos, C; Rojas-Rojas, S (Springer Netherlands, 2019)
Studies have investigated various aspects of the use of questions in science lessons, but there is still a lack of research that demonstrates how, during peer reflection, teachers learn through identifying and overcoming obstacles to their own questioning in their professional development process. The present study is aimed at analyzing the types of obstacles identified by science teachers who participated in a Teacher Reflection Workshop (TRW) on the formulation and use of questions in their lessons. The workshop consisted of stage 1 (7 sessions), stage 2 (video recordings in school classrooms), and stage 3 (3 sessions). The discourses of 8 participating teachers in the areas of chemistry, biology, physics, and natural science at different educational institutions in the city of Santiago, Chile, were analyzed in this case study. The analysis was carried out by the professors participating in the workshop, based on the participants’ identification, initial attempts to address, and proposals to overcome, their obstacles. In the earlier stages of the process, the identified obstacles had procedural characteristics, but as the process advanced, they took on a more epistemological nature. One of the main differences between the initial and final identification of obstacles by the participating teachers is that the latter were more precise and critical, and the teachers increasingly demonstrated the ability to propose specific solutions to teaching problems. Engagement with the obstacles does not take place uniformly but depends on the types of obstacles that the teachers identify in their practice. Proposals for overcoming the obstacles require the teachers to have time for reflecting and validating their ideas in their practice. © 2019, Springer Nature B.V.